Optical, Electrical and Raman Properties of Annealed Hydrogenated Mg/Co Bilayer Thin Films - M. Singh; S.P. Nehra; M.K. Jangid (Журнал нано- та електронної фізики)
Bilayer Mg/Co thin films prepared using thermal evaporation method at pressure 10 – 5 torr at room temperature. The films were rapid thermal annealed (RTA) using halogen lamp for different times to get a homogeneous structure of Mg/Co thin films. The hydrogen gas was introduced in hydrogen chamber, where samples were kept at different pressure of H2 for thirty minutes. The UV–VIS transmission spectra of annealed and annealed hydrogenated films have been carried out at room temperature in the wavelength range of 300-800 nm. The optical band gap was found to be increased due to hydrogenation and decrease with annealing time and also conductivity has been found to be decreased with hydrogen and increased with annealing time. Raman spectra show decreasing intensity of peaks with annealing and hydrogenation. Relative resistivity varies nonlinearly with time and decreases with annealing time. Surface morphology of annealed and annealed hydrogenated bilayer thin films has been confirmed by optical microscopy.